What good leaders actually do: micro-level leadership behaviour, leader evaluations, and team decision quality. Issue 6 (1st November 2016) - Meyer, Bertolt; Burtscher, Michael J.; Jonas, Klaus; Feese, Sebastian; Arnrich, Bert; Tröster, Gerhard; Schermuly, Carsten C.
Abstract : We supplement broad definitions of leadership behaviour with the concept of micro-level leadership behaviour, leaders' verbal and non-verbal visible conduct and interaction. For the context of team decision-making, we identify two potentially beneficial micro-level leadership behaviours, question asking and behavioural mimicry. Specifically, we propose that under conditions of informational complexity and unshared information, participative leadership is most appropriate for team decision-making, that its effects are mediated by inquiring and empathy, and that question asking and mimicry are the behavioural micro-level manifestations of inquiring and empathy. We thus hypothesize that the effect of participative leadership on team decision quality and leader evaluation is mediated by question asking and mimicry. We conduct a laboratory experiment with student teams working on a hidden profile decision-making task and measure question asking through behavioural coding and mimicry with motion sensors. Results show that the effect of participative leadership on decision quality is mediated by question asking, and that the effect of participative leadership on leader evaluation as transformational is mediated by leaders' behavioural mimicry and question asking. Under control of these micro-level behaviours, team decision quality and leader evaluations were unrelated.